Nonparametric analysis of the mixed-demand model - Per Hjertstrand (Research Institute of Industrial Economics (IFN), 2022)
The mixed-demand model allows for very flexible specification of what should be considered endogenous and exogenous in demand system estimation. This paper introduces a revealed preference framework to analyze the mixed-demand model. The proposed methods can be used to test whether observed data (with measurement errors) are consistent with the mixed-demand model and calculate goodness-of-fit measures. The framework is purely non-parametric in the sense that it does not require any functional form assumptions on the direct or indirect utility functions. The framework is applied to demand data for food and provides the first nonparametric empirical analysis of the mixed-demand model.
Keywords: D11; D12; 330; demand systems; measurement errors; mixed-demand; non-parametric; revealed preference